Creating passion-driven teams : how to stop micromanaging and motivate people to top performance - Bobinski, Dan (Career Press, 2009)
Can passion be taught? Can it be fostered? The answer is yes. But perhaps more accurately, a team leader must create the right conditions for passion to emerge. Those conditions must be nurtured, not unlike a gardener creating the right conditions for his plants to flourish. Make your job easier. Get the inside scoop on the secrets of success that motivate teams to top performance. In the matrix of workplace roles and responsibilities, managers are pivotal to corporate success. Yet a manager is often the unsung hero who must adapt to demands from all sides -- and do so with little or no training, and without mentorship for the role. Learn from Dan Bobinski, who draws from 20 years of consulting experience, extensive studies of best practices, and the latest in neuroscience research. You'll learn the principles and methods top managers use to develop passionate, engaged employees who are dedicated to success. You'll be able to: -Motivate without manipulating -Turn mistakes into a fervent drive for quality -Equip teams to enthusiastically adapt to change -Create environments in which people strive for excellence -- and more Today's workforce requires managers to be more than just a person in charge. Creating Passion-Driven Teams show you how to tap your team's natural motivations and achieve consistent, sustained top performance. Dan Bobinski is the president and CEO of Leadership Development, Inc., and director at the Center for Workplace Excellence. For more than 20 years Dan has coached and trained managers and leaders in the Fortune 500 as well as small and mid-sized businesses. His Workplace-Excellence blog has been listed among the top 100 daily must-reads for entrepreneurs, and his newspaper column on workplace issues is syndicated internationally. Dan is a passionate speaker and trainer on management topics, and he holds a master's degree in human resource training and development as well as a BS in workforce education and development. Dan lives in Boise, Idaho.